The Development Of Islamic Capital Markets In Indonesia - Syahmina Hamimi; Yogi Rahman Feriza Ginting (Proceeding International Seminar of Islamic Studies, 2019)
This paper is an attempt to analytically describe the stocks and capital markets in Islamic perspective. In so doing, this paper tries to elaborate Reviews their implementation in the financial sectors in Indonesia. One of the instruments of Islamic finance is islamic stocks. The Jakarta Islamic Index (JIT) has been used in the Jakarta Stock Exchange since 2000, Although Indonesia Islamic Capital Market Officially Launched on march, 14, 2003. The performance of Islamic capital market products in general show a good enough growth. From the legal aspect, the Islamic capital market in Indonesia still need regulation. The mechanism of capital markets have to completed to Prevent the entrance of usury maysir, and ghorar practices.Capital market players are 1. Issuers, 2 Investors, 3. Fund Management Companies (Investment Company), 4. Mutual Funds, 5. Capital Market Support Institutions and Products in the Islamic Capital Market; 1. Stocks Islamic, Islamic Bonds 2., 3. Islamic Mutual Funds.